AOIΔIMOI AΘANAI. Pochwała Aten w poezji Pindara - Magdalena Stuligrosz (Collectanea Philologica, 2020)
The prescriptions on how to eulogize the city, provided in 3rd century by Menander Rhetor in his treatise On Epideictic, reflect the encomiastic convention according to which Pindar composed his poetic encomia urbis. Among the topoi that the poet applies to praise Athens one can list the ancient origin of the city, including the identification of its founder, the practiced habits concerning the form of politeia as well as those concerning the professional skills and abilities of the inhabitants, their virtues and deeds in war and in peace.